2021
DOI: 10.1124/jpet.121.000629
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase Inhibition Enhances Dimerization of Calreticulin at the Cell Surface in Mitoxantrone-Induced Immunogenic Cell Death

Abstract: ICD -immunogenic cell death DAMPs -danger-associated molecular patterns DCs -dendritic cells MTX -mitoxantrone PERK -protein kinase RNA-like endoplasmic reticulum kinase eIF2α -eukaryotic initiating factor 2α CRT -calreticulin ectoCRTcell surface exposed CRT Cer -ceramide S1P -sphingosine-1-phosphate Sph -sphingosine dhSph -dihydroSph CerS1-6 -ceramide synthases 1-6 SphKs -sphingosine kinases SKIs -SphK inhibitors SRB -Sulforhodamine BThis article has not been copyedited and formatted. The final version may di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…The copyright holder for this preprint this version posted September 18, 2021. ; https://doi.org/10.1101/2021.09.16.460650 doi: bioRxiv preprint Sphingosine kinase inhibition enhances the production of ectoCRT by non-effective doses of ABT/AZD. We have previously demonstrated that inhibition of sphingosine kinase 1 and/or 2 (SphK1/2) enhances ectoCRT production by the known ICD-inducing agent mitoxantrone MTX through accumulation of ceramide (Cer) 2 . Bak, as well as Bax have been associated with induction of Cer synthesis through multiple studies 7,8,20 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted September 18, 2021. ; https://doi.org/10.1101/2021.09.16.460650 doi: bioRxiv preprint Sphingosine kinase inhibition enhances the production of ectoCRT by non-effective doses of ABT/AZD. We have previously demonstrated that inhibition of sphingosine kinase 1 and/or 2 (SphK1/2) enhances ectoCRT production by the known ICD-inducing agent mitoxantrone MTX through accumulation of ceramide (Cer) 2 . Bak, as well as Bax have been associated with induction of Cer synthesis through multiple studies 7,8,20 .…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that MTX, a well characterized inducer of ICD causes Cer accumulation through recycling of Sph to form Cer. Inhibition of the SphKs blocked conversion of Sph to S1P and further enhanced Cer formation and production of dimeric ectoCRT 2 . Elsewhere, we have demonstrated that synthetic cannabinoids induce ICD through induction of de novo synthesis of Cer and that inhibition of the SphKs enhances these effects (manuscript submitted to Cannabis and Cannabinoids Research).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of cell surface exposure of CRT was described previously [ 2 ]. Briefly, cells were seeded at about 3 × 10 5 cells/well in six well plates in complete DMEM for 24 h, then transferred to DMEM containing 5% FBS and penicillin/streptomycin in the presence of treatments for 48 h. Cells were collected by trypsinization, followed by three washes in PBS containing 2% FBS, stained with anti-calreticulin (D3E6) phycoerythrin (PE) conjugated antibody at 4 °C for 1 h, washed as above, and CRT was detected by Muse cell analyzer (SmartFlare detection settings).…”
Section: Methodsmentioning
confidence: 99%
“…While modulation of immunosuppression in the TME suggests a potential therapeutic benefit for SphK inhibition as part of the armament against cancer, we recently discovered a previously unrecognized role for sphingolipids as regulators of cancer cell immunogenicity [ 2 ]. To this end, we demonstrated that inhibition of SphK1 and/or SphK2 and therefore, S1P production, leading to ceramide (Cer) accumulation enhances the ability of certain chemotherapies (e.g., mitoxantrone) to induce a specific form of regulated cell death termed immunogenic cell death (ICD).…”
Section: Introductionmentioning
confidence: 99%